PERANCANGAN MODUL SOFT START DENGAN POWER METER INDIKATOR BERBASIS ARDUINO DAN PZEM-004T UNTUK INDUSTRI RUMAH TANGGA - Irsyad Hadi Rahmanto; Ojak Abdul Rozak (Electro Luceat, 2025)
Electricity is a basic necessity at the household level. Households tend to overlook factors that cause power surges, such as the use of electrical loads that incrush current when turned on. One device that can reduce a incrush current during start-up is softstart. The purpose of this design and testing is to reduce current during the startup of electrical loads and to determine the values of current and electrical energy efficiency before and after the use of the softstart module in real time. The method is design softstart module and powermeter indicator based on Arduino and PZEM-004T. The results show that the voltage at the softstart module output is still within PLN tolerance standards. The voltage and current in test using module for resistive and inductive loads are lower and have an efficiency value of 95% for resistive loads and 94% for inductive loads. The incrush current in both loads increases gradually with a small current value. The conclusion of the study is that the softstart module can reduce starting incrush currents, power consumption, and has good efficiency values. The design of measurement device based on Arduino Uno and the PZEM-004T sensor produced accurate voltage and current measurements.